The Influence of Job Satisfaction and Work Motivation on Organizational Commitment in Lecturers of The Faculty of Economics and Business at Swadaya Gunung Jati University - Edy Hartono (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aims to determine the effect of job satisfaction and work motivation on the organizational commitment of the Faculty of Economics and Business, Swadaya Gunung Jati University's lecturer. In this type of research, researchers use associative research. The use of this research method uses quantitative methods. Software using SPSS version 23. In taking this sample, the researcher used a saturated sample technique. Because of the Faculty of Economics and Business, Swadaya Gunung Jati University's lecturer population is only 88. The results showed that job satisfaction and work motivation influenced organizational commitment either partially or simultaneously.